2019
DOI: 10.1002/ejp.1506
|View full text |Cite
|
Sign up to set email alerts
|

The effects of long‐term opioid treatment on the immune system in chronic non‐cancer pain patients: A systematic review

Abstract: Background and objective Opioids have been increasingly prescribed for chronic non‐cancer pain (CNCP). An association between long‐term opioid treatment (L‐TOT) of CNCP patients and suppression of both the innate and the adaptive immune system has been proposed. This systematic review aims at investigating the effects of L‐TOT on the immune system in CNCP patients. Databases and data treatment A systematic search of MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials and the CINAHL for relevant art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 45 publications
0
22
0
3
Order By: Relevance
“…with variable results on perceived pain [ 7 , 8 , 9 ]. Despite these promising results, research has suggested that 64% of patients with persistent pain feel that remaining on opioid medications are worth the risk of harm (e.g., potential impact on immune system) [ 39 , 40 ]. This belief may hinder implementation of alternative pain management methods such as exercise and meditation that were recommended by pharmacists during this study.…”
Section: Discussionmentioning
confidence: 99%
“…with variable results on perceived pain [ 7 , 8 , 9 ]. Despite these promising results, research has suggested that 64% of patients with persistent pain feel that remaining on opioid medications are worth the risk of harm (e.g., potential impact on immune system) [ 39 , 40 ]. This belief may hinder implementation of alternative pain management methods such as exercise and meditation that were recommended by pharmacists during this study.…”
Section: Discussionmentioning
confidence: 99%
“…For example, if more MCP in women is associated with immune function, drugs that influence this may have specific long-term effects (positive or negative) in women and not in men. Opioids are known to adversely affect immune function (105,106). These differences may also inform the search for new, or re-purposed drugs in a sex specific manner, building on animal studies where specific proteins have been found to play sex-specific roles in pain processing, and certain drugs have been found to have sex-specific effects in terms of analgesia (reviewed by (107)).While there are clearly also many similarities, it is important that clinicians begin to recognize these differences in clinical assessment and awareness of risks.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of opioid receptor acting drugs are currently FDA‐approved in the US with a vast number of immunologic actions (Table 1). 16,17 …”
Section: Methodsmentioning
confidence: 99%